PENERAPAN PARIWISATA BERBASIS MASYARAKAT DALAM PENGELOLAAN DESA WISATA BULUH CINA KABUPATEN KAMPAR - Fadiyah Humairo; Firdaus Yusrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2026)
The concept of Community Based Tourism has been reflected in the management of Buluh Cina Tourism Village, Kampar Regency. This study aims to examine in depth how the community implements tourism management in Buluh Cina Tourism Village and to identify the stakeholders involved in the process. This research employs a qualitative case study approach through interviews, observations, and documentation to gain a comprehensive understanding of the phenomenon. The results show that Buluh Cina Tourism Village possesses diverse natural resources and strong local wisdom that remain embedded in the daily lives of the community, which are utilized as various tourism activities. In its management, the community is involved across different groups, including the general community acting as tourism actors, youth groups promoting the tourism village, and vulnerable groups such as the elderly and children as beneficiaries of tourism activities. The management practices have integrated social, environmental, and cultural aspects; however, the economic benefits have not yet been sustainably experienced by the community. The study also identifies several complex challenges in its management, including the less optimal role of the tourism awareness group (Pokdarwis), the dominance of external stakeholders, ineffective community training programs, and the lack of sustainable community-based economic products. These findings indicate that the success of a tourism village that involves the community as the main actor also requires consistent local institutional support, targeted human resource development, and clear economic development strategies. Keywords: Community Based Tourism, Buluh Cina Tourism Village, Tourism Village Management, Local Community